Metabolic rate and critical thermal maximum CTmax estimates for westslope cutthroat trout, Oncorhynchus clarkii lewisi. Issue 1 (21st December 2022) - Enders, Eva C; Durhack, Travis C
Abstract : We measured metabolic rates of adult native westslope cutthroat trout and non-native rainbow trout and the critical thermal maximum of adult westslope cutthroat trout. The results will inform and parametrize models used in the recovery planning of westslope cutthroat trout. Abstract: Global warming is changing the thermal habitat of cold-water freshwater fishes, which can lead to decreased fitness and survival and cause shifts in species distributions. The Alberta population of westslope cutthroat trout ( Oncorhynchus clarkii lewisi ) is listed as 'Threatened' under the Canadian Species at Risk Act . The major threats to the species are the alteration in habitat and water flow, competition and hybridization with non-native trout species and climate change. Here, we conducted (i) intermittent-flow respirometry experiments with adult native westslope cutthroat trout and non-native rainbow trout ( Oncorhynchus mykiss ) and (ii) critical thermal maximum experiments ( CTmax ) with adult westslope cutthroat trout to obtain valuable input data for species distribution models. For both species, standard metabolic rate (SMR) was lower at 10°C compared to 15°C and westslope cutthroat trout had higher SMR than rainbow trout. Although there were inter-specific differences in SMR, forced aerobic scope (using a standardized chase protocol) was different at 10°C, but no significant differences were observed at 15°C because of relative smaller differences in maximum metabolic rate between the species. CTmax of westslope cutthroat trout acclimated to 10°C was 27.0 ± 0.8°C and agitation temperature was 25.2 ± 1.0°C. The results from this study will inform and parametrize cumulative effects assessments and bioenergetics habitat modelling for the recovery planning of the species.